Phytochemical Screening of Ficus glomerata. Roxb. Galled leaves - Sudhakar, A (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTFicus glomerata. Roxb. commonly called as â€œFig treeâ€ is traditionally popular for its medicinal properties. The psyllid insect Pauropsylla depressa was identified in the present study to induce leaf galls in F. glomerata. Preliminary phytochemical screening of the various extracts of galled leaves in F.glomerata showed the presence of alkaloids, steroids, quinones and phenols in addition to fluorescence compounds. The therapeutic properties of these phytochemicals and their pharmacological significance are outlined.